HUBUNGAN PENGETAHUAN DENGAN PERILAKU PERINEAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI - Manoppo, Ivanna; Dwiyanti, Sagita (Fakultas Keperawatan, Universitas Klabat, 2025)
The behavior of maintaining cleanliness of the perineal area (perineal hygiene) during menstruation is an important factor in maintaining cleanliness and reproductive health, especially in adolescent girls to prevent the risk of infection in the genital area. Many adolescent girls have sufficient knowledge, but it has not been followed by the correct behavior in maintaining genital hygiene during menstruation. This study aims to determine the relationship between knowledge and perineal hygiene behavior during menstruation in adolescent girls. The research method employed a descriptive correlation with a cross-sectional study design. A total of 129 samples were collected using purposive sampling. The results showed that 17 participants (13.2%) had good knowledge, 90 participants (69.8%) had sufficient knowledge while 22 participants (17.1%) had insufficient knowledge. Perineal hygiene behavior during menstruation was found to be 68 participants (52.7%) showed good behavior while 61 participants (47.3%) showed insufficient behavior. The statistical test results revealed a p-value of 0.231, which is greater than the significance level of 0.05. This indicates that there is no significant relationship between knowledge and perineal hygiene behavior during menstruation among adolescent girls. Recommendations for adolescent girls include increasing awareness and maintaining good genital hygiene habits during menstruation to prevent infection. This research is also expected to serve as a baseline for further studies, considering external (cultural) and internal (developmental level, habits) factors that may influence perineal hygiene behavior. Perilaku menjaga kebersihan area perineum (perineal hygiene) selama menstruasi merupakan faktor penting dalam menjaga kebersihan dan kesehatan reproduksi, khususnya pada remaja putri untuk mencegah risiko infeksi pada area genital. Banyak remaja putri memiliki pengetahuan yang cukup, tetapi belum diikuti oleh perilaku yang benar dalam menjaga kebersihan area genital saat menstruasi. Penelitian ini bertujuan mengetahui hubungan antara pengetahuan dengan perilaku perineal hygiene saat menstruasi pada remaja putri. Metode penelitian menggunakan deskriptif korelasi dengan desain penelitian cross sectional dengan 129 sampel yang diambil menggunakan teknik purposive sampling. Hasil penelitian menunjukkan 17 partisipan (13,2%) memiliki pengetahuan baik, 90 partisipan (69,8%) memiliki pengetahuan cukup sedangkan 22 partisipan (17,1%) mempunyai pengetahuan kurang. Perilaku perineal hygiene saat menstruasi didapati 68 partisipan (52,7%) menunjukkan perilaku baik sedangkan 61 partisipan (47,3%) menunjukkan perilaku yang kurang. Hasil uji statistik spearman rank didapati p-value = 0,231 > 0,05, menunjukkan tidak ada hubungan yang signifikan antara pengetahuan dengan perilaku perineal hygiene saat menstruasi pada remaja putri. Rekomendasi bagi remaja putri meningkatkan kesadaran dan kebiasaan menjaga kebersihan area genital selama menstruasi untuk mencegah infeksi. Penelitian ini juga diharapkan menjadi acuan awal bagi studi selanjutnya, dengan mempertimbangkan faktor eksternal (budaya) dan internal (tingkat perkembangan, kebiasaan) yang dapat mempengaruhi perilaku perineal hygiene.